2005
DOI: 10.1096/fj.05-3907fje
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin is neuroprotective, improves functional recovery, and reduces neuronal apoptosis and inflammation in a rodent model of experimental closed head injury

Abstract: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality in young people in industrialized countries. Although various anti-inflammatory and antiapoptotic modalities have shown neuroprotective effects in experimental models of TBI, to date, no specific pharmacological agent aimed at blocking the progression of secondary brain damage has been approved for clinical use. Erythropoietin (Epo) belongs to the cytokine superfamily and has traditionally been viewed as a hematopoiesis-regulating hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
171
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 61 publications
9
171
0
6
Order By: Relevance
“…Such a model mimics several pathophysiological characteristics of human focal cortical contusion (Nag, 1996) and produces a reproducible, demarcated lesion to the neocortex that allows evaluation of the efficacy of compounds with a neuroprotective potential (Hortobagyi et al, 2000). The present findings extend previous work by showing that rHuEPO significantly reduces brain injury and improves neurological recovery following traumatic insults (Brines et al, 2000;Lu et al, 2005;Ozturk et al, 2005;Shein et al, 2005;Siren et al, 2006;Verdonck et al, 2007;Yatsiv et al, 2005). In particular, rHuEPO administration improved both functional and cognitive recovery of the rats with an effect that was significantly shown since the early stage after TBI and lasted for 15 days.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Such a model mimics several pathophysiological characteristics of human focal cortical contusion (Nag, 1996) and produces a reproducible, demarcated lesion to the neocortex that allows evaluation of the efficacy of compounds with a neuroprotective potential (Hortobagyi et al, 2000). The present findings extend previous work by showing that rHuEPO significantly reduces brain injury and improves neurological recovery following traumatic insults (Brines et al, 2000;Lu et al, 2005;Ozturk et al, 2005;Shein et al, 2005;Siren et al, 2006;Verdonck et al, 2007;Yatsiv et al, 2005). In particular, rHuEPO administration improved both functional and cognitive recovery of the rats with an effect that was significantly shown since the early stage after TBI and lasted for 15 days.…”
Section: Discussionsupporting
confidence: 79%
“…Although the role of EPO as a neuroprotectant has been studied extensively in a wide range of in vitro and in vivo models of brain injury, up to date, there are only few studies evaluating the effect of rHuEPO after experimental TBI (Brines et al, 2000;Lu et al, 2005;Ozturk et al, 2005;Shein et al, 2005;Siren et al, 2006;Verdonck et al, 2007;Yatsiv et al, 2005) and none has used a cryogenic injury paradigm. Neurobehavioral improvement after EPO administration has been reported in other studies where different models of brain injury were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent accumulation of proinflammatory cytokines further aggravates the impairment (Das, Mohapatra, & Mohapatra, 2012). The ability of EPO to improve cognitive outcome has been demonstrated by our study as well as other researchers (Barichello et al., 2014; Yatsiv et al., 2005). Previous studies have shown that EPO promotes angiogenesis and increases cerebral blood perfusion (Meng et al., 2011).…”
Section: Discussionmentioning
confidence: 99%